How Sensitivity of Energy Intake to Fuel Price Change: Evidence from Central Java - Widarjono, Agus (Muhammadiyah University Press, 2018)
Because of high world oil prices during 2008-2013, the government must adjust domestic fuel price several times. One of the fuel price adjustments occurred in 2013. The increase in fuel prices caused high inflation. The purpose of this study is to analyze the impact of rising fuel prices on calorie consumption as a main source of energy intakeÂ in Central Java Province. The results of this study indicate that calorie income elasticity increased both in urban and rural areas after the increase in fuel price. However, urban households are more responsive than rural households. An increase in calorie income elasticity means that households must allocate more expenditure on food consumption in order to fulfill minimum energy intake. These findings imply that cash transfer policies such as direct cash transfer for poor households known as BLT as well as rice policy for poor households as called Raskin are very effective to maintain minimum calorie intake during price crisis.